From conjugation to T4S systems in Gram‐negative bacteria: a mechanistic biology perspective. (2nd January 2019) - Waksman, Gabriel
Abstract: Conjugation is the process by which bacteria exchange genetic materials in a unidirectional manner from a donor cell to a recipient cell. The discovery of conjugation signalled the dawn of genetics and molecular biology. In Gram‐negative bacteria, the process of conjugation is mediated by a large membrane‐embedded machinery termed "conjugative type IV secretion (T4S) system", a large injection nanomachine, which together with a DNA‐processing machinery termed "the relaxosome" and a large extracellular tube termed "pilus" orchestrates directional DNA transfer. Here, the focus is on past and latest research in the field of conjugation and T4S systems in Gram‐negative bacteria, with an emphasis on the various questions and debates that permeate the field from a mechanistic perspective. Abstract : In Gram‐negative bacteria conjugation is mediated by a large membrane‐embedded nanomachine of the type IV secretion (T4S) system. This review highlights recent research on conjugation and T4S systems, and provides a comprehensive structural and mechanistic overview.